2017
DOI: 10.22159/ijpps.2017v9i2.14374
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Activities of Rubus Fruticosus and Zizyphus Vulgaris Methanol Extracts

Abstract: Objective: This report is an attempt to study the phenolic composition of Rubus fruticosus (RFE) and Zizyphus vulgaris (ZVE) methanol extracts and evaluate their antioxidant and anti-inflammatory effects in-vitro and in-vivo. Methods:Total phenolic and total flavonoids contents of extracts were determined by spectrophotometric methods. Phenolic compounds were identified by HPLC-TOF/MS. The antioxidant activities were evaluated in vitro using DPPH, ABTS and FRAP assays. The effect of RFE and ZVE on DNA cleavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Antiradical activity of phenylalyl derivative 13 remains at 90%. In general, the following should be noted: The highest antioxidant effect was observed for 1-(1,3-dimethyl-2,6-dioxo-7-arylalkyl-(alkenyl-)-2,3,6,7-tetrahydro-1H-purine-8-yl)-5-(4-methoxyphenyl)-1H-pyrazole-3-carboxylates (11)(12)(13), which is consistent with the literature data [13].…”
Section: Activity On the In Vitro Model Of Inhibition Of Soybean Liposupporting
confidence: 91%
See 1 more Smart Citation
“…Antiradical activity of phenylalyl derivative 13 remains at 90%. In general, the following should be noted: The highest antioxidant effect was observed for 1-(1,3-dimethyl-2,6-dioxo-7-arylalkyl-(alkenyl-)-2,3,6,7-tetrahydro-1H-purine-8-yl)-5-(4-methoxyphenyl)-1H-pyrazole-3-carboxylates (11)(12)(13), which is consistent with the literature data [13].…”
Section: Activity On the In Vitro Model Of Inhibition Of Soybean Liposupporting
confidence: 91%
“…When DPPH interacts with substances that capable of binding to free radicals, produce products that are mostly colored in shades of yellow and do not absorb light at the above wavelength. This method is fast, easy to implement and allows for the screening of large arrays of investigated substances [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…While working with Turkish Tea polyphenols and alkaloid Erol et al [30] proposed that alkaloid content is linked with antioxidant activity. Rackova et al [31][32][33] suggested that probably high lipophilicity of the alkaloids is responsible for antiradical reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum radical scavenging activity was exhibited by the acetone extract of P. longifolia implying that phenol and flavonoid content is positively correlated to the antioxidant activity of a plant [16][17][18]. Considering evidence from literature [19][20][21][22], the involvement of phenols and flavonoid in antioxidant activity can be established. Thus, the present findings in this context, summarizes with the same concept without any deviation.…”
Section: Discussionmentioning
confidence: 97%